ANALISIS PENGARUH PENGELUARAN PEMERINTAH DAN PAJAK DAERAH TERHADAP PRODUK DOMESTIK REGIONAL BRUTO KABUPATEN/KOTA PROVINSI KALIMANTAN TIMUR TAHUN 2013-2017 - Salshabilla Nafitri Shafarilla; Zainal Arifin (Program Studi Ekonomi Pembangunan, 2019)
The purpose of study to determine the effect of government spending and local taxes on the economic growth of Regency/Cities of East Kalimantan Province in 2013-2017. The method used in this research is panel data consisting of 7 districts and 3 cities in East Kalimantan Province for 5 years (2013-2017). The test results show that the best model selection used in this study is the Fixed Effects (FE) model. The results of the research obtained show that government expenditure variables have a positive and significant effect on the growth of the Regency/Cities of East Kalimantan Province. While the regional tax variable shows positive and significant results also on the economic growth of the Regency/Cities of East Kalimantan Province.